Sexting in youth: The psychological phenomenon and its intersubjectivity revealed in contemporary music narratives contemporary (Research, Society and Development, 2024)
Sexting arises from the practice of relationships experienced in the midst of virtual technologies, when the sharing of text messages – photographs, and videos of an intimate and erotic character called “nudes”, signals different problems. It aims to analyze from the materiality, sexting as a psychological phenomenon, and its intersubjectivity. It is a qualitative bibliographic research, based on scientific articles and a descriptive-exploratory study that elucidates its characteristics, familiarity, and developments. Furthermore, it was known about the specificities of this practice of connecting with others and its variables revealed in the sexual / virtual context: nudity, impulsiveness, needs, desires, fads, freedom, innovation, rupture of regulatory standards, immaturity, internet crimes, revenge porn, etc. The discussion will be articulated through the narratives of contemporary music. It is necessary to understand the use of the internet by adolescents/young people, to identify the influencing variables in the evolutionary cycle: exhibitionism, supremacy of superficial and “liquid” relationships, devaluation of real affections, provocative and unassuming dialogues.